Antifungal Activity of Denture Base Resin Containing Nanozirconia: In Vitro Assessment of Candida albicans Biofilm. (2nd August 2021) - Abualsaud, Reem; Aleraky, Doaa M.; Akhtar, Sultan; Khan, Soban Q.; Gad, Mohammed M.
Abstract : Objective . To evaluate the antimicrobial effects of different concentrations of zirconium dioxide nanoparticles (nano-ZrO2 ) reinforcement of poly(methyl) methacrylate (PMMA) on surface roughness and C. albicans biofilm. Methods . 20 heat-polymerized acrylic resin discs were conventionally made and divided into 4 groups ( n = 5) according to nano-ZrO2 concentration: control (0% filler) and 3 experimental groups (2.5% (Z2.5), 5.0% (Z5.0), and 7.5% (Z7.5)). An optical profilometer was used for surface roughness evaluation, followed by Candida adherence assay. Specimens were sterilized, then immersed in cultured yeast ( C. albicans ), and incubated at 37°C for 48 hours. After that, discs were rinsed before extracting the clustered pellets of Candida. The attached C. albicans was counted using the direct method after spreading on agar media and incubating for 48 hours. Statistical analysis was performed using one-way ANOVA and Tukey's post hoc test at α = 0.05. Results . Surface roughness was significantly increased with all modified groups compared with control (P < 0.01 ), which showed the lowest roughness value (0.027 ± 0.004 μ m). There was no significant difference in the roughness value among reinforced groups (2.5, 5.0, and 7.5%) (P > 0.05 ), with Z7.5 showing the highest roughness value (0.042 ± 0.004 μ m). Candida count was reduced as the nano-ZrO2 increased but not significantly (P = 0.15 ). Conclusions . The addition of different concentrations of nano-ZrO2 particles to PMMA increased the surface roughness compared with control; in contrast, insignificant reduction of C. albicans biofilm was detected.